Homo digitalis – Homo medialis. Digitális média és keresztyén antropológia - KOVÁCS, Krisztián (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2021)
Homo Digitalis – Homo Medialis. Digital Media and Christian Anthropology. Digital media and virtual community existence define our present and our everyday life to such an extent and poses such new challenges that Christian ethics cannot escape the responsibility of guidance. However, it is not just a question of what ethical norms apply to the online space and appearance therein but also of how online identity redraws a person’s image of him-/herself and of the other. Can Christian ethics speak of homo digitalis and homo medialis without confronting Christian teaching about humans? The present study seeks to critically illuminate new phenomena in the digital world along the topoi of classical Christian anthropology (creation, divinity, alienation, shame, sin, fellow human beings).